2015
DOI: 10.5492/wjccm.v4.i2.105
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulant modulation of inflammation in severe sepsis

Abstract: Inflammation and coagulation are so tightly linked that the cytokine storm which accompanies the development of sepsis initiates thrombin activation and the development of an intravascular coagulopathy. This review examines the interaction between the inflammatory and coagulation cascades, as well as the role of endogenous anticoagulants in regulating this interaction and dampening the activity of both pathways. Clinical trials attempting to improve outcomes in patients with severe sepsis by inhibiting thrombi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 55 publications
(84 reference statements)
2
57
0
4
Order By: Relevance
“…We will not consider this important subject here as, while vitamin K is required for generation of the mature functional protein, it is the role of protein C as a serine protease that is central to the mechanism of limiting microthrombus formation in organ tissue beds in sepsis [14].…”
Section: Vitamin K and Inflammationmentioning
confidence: 99%
“…We will not consider this important subject here as, while vitamin K is required for generation of the mature functional protein, it is the role of protein C as a serine protease that is central to the mechanism of limiting microthrombus formation in organ tissue beds in sepsis [14].…”
Section: Vitamin K and Inflammationmentioning
confidence: 99%
“…Varios elementos de la coagulación participan en la amplifi cación de la respuesta infl amatoria, por ejemplo, las plaquetas reconocen PAMPs y DAMPs mediante los receptores TLR4 expuestos en su superfi cie y al hacerlo son capaces de presentar los microorganismos y antígenos a los neutrófi los dando lugar a la respuesta inmune mediada por ellos ya descrita (52). Ahora bien, la DIC, considerada como el más importante marcador de pobre pronóstico en sepsis, se caracteriza por una masiva producción de trombina, acelerado consumo activación de plaquetas, deterioro de la fi brinó-lisis y trombosis microvascular, lo cual es originado en la sepsis a través de la generación de factor tisular mediador de trombina o factor tisular intravascular (TF), disminución de mecanismos anticoagulantes como son la antitrombina (AT), proteína C activada (APC) y el factor tisular inhibidor (TFPI); y daño de la fi brinólisis.…”
Section: Ifn-γunclassified
“…La Proteína C es activada en condiciones normales, por la trombina unida a la trombomodulina y por el receptor endotelial de la proteína C (EPCR) en las células endoteliales, una vez se disocia de su receptor de une a la proteína S logrando inactivar los factores de coagulación Va y VIIIa, además disminuye la apoptosis de células endoteliales y linfocitos e inhibe el PAI -1; en la sepsis es inhibida por la HMGB1 que interfi ere en la unión de la trombina -trombomodulina. Otro evento de la coagulación que explica fenómenos de la sepsis es el hecho de que en las plaquetas activadas se expresa la P -selectina luego de que han sido expuesta a la trombina y esto media la unión de los leucocitos a las células endoteliales y su activación contribuyendo a la lesión difusa de la microvasculatura que explica el daño orgánico ya mencionado (11,52,53).…”
Section: Ifn-γunclassified
“…When stasis occurs, an amorphous material, chylomicra or thrombi of platelets, and necrotic debris clog the vascular lumen [56] . Animal studies have shown that the presence of infection and sepsis induces a significant increase in thrombosis and distant pyogenic abscesses [56][57][58] . Autopsy cases have shown pulmonary microthrombi and partially dissolved fibrin in vessels of burn patients contributing to sludging of cells in vessels [59] .…”
Section: Thrombosis and Thromboembolismmentioning
confidence: 99%